Profile of Concept Understanding and Scientific Argumentation Skills on Genetic Material of Grade XII MIPA Students of SMA Laboratorium UM - Biruni, Iqbal Bilgrami; Suwono, Hadi; Muntholib, Muntholib (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2024)
Scientific argumentation skills as an intellectual practice can involve students in constructing and criticizing scientific ideas related to science literacy. The purpose of this study is to find out the scientific argumentation ability of high school students with different conceptual understandings. This study was designed as a survey involving students in grade XII of MIPA SMA Laboratorium UM. The results show that the highest average value of understanding the concept of genetic material was 87,22 and the lowest average value was 69,00. Indicator of scientific argumentation